Використання освітнього порталу в дистанційному навчанні: недоліки й переваги - Шарова, Тетяна Михайлівна; Землянська, Аліна Вікторівна; Sharova, Tetiana; Zemlianska, Alina (Запоріжжя : 2023, 2023)
UA: Стаття аналізує досвід використання Освітнього порталу ТДАТУ в дистанційному навчанні в умовах воєнного стану. Визначено переваги й недоліки єдиної онлайн-платформи університету з метою вдосконалення освітнього процесу в онлайн-режимі. EN: The article analyzes the experience of using the Educational Portal of TDATU in distance learning in the state of the war. The advantages and disadvantages of the university's single online platform are determined in order to improve the educational process in the online mode.
Using the Educational Portal in distance education: disadvantages and advantages
Keywords: освітній портал; онлайн-платформа; дистанційне навчання; електронна система; електронний навчальний курс; Educational Portal; online platform; distance learning; electronic system; electronic training course